How Anthropomorphism And Initial Trust Shape Chatbot Customer Experience? The Moderating Role Of Technology Anxiety (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Based on the stimulus-organism-response (SOR) model, this study aims to investigate the effect of anthropomorphism and initial trust on customer experience. It also assesses the moderating effect of technology anxiety on the relationship between anthropomorphism and customer experience, which remains underexplored. Data were collected from 385 Tunisian students and analyzed using partial least squares structural equation modeling. Results indicate that anthropomorphism has a positive influence on both initial trust and customer experience, and that initial trust has a positive effect on customer experience. Findings also reveal that technology anxiety negatively moderates the relationship between anthropomorphism and customer experience. This study provides valuable insights for managers and system developers.